Interaction Study of 2-Benzoxazolinone Derivatives with DPP-4 and Aldose Reductase Enzymes: Discovery of Novel Antidiabetic Agents - Aziez Ismunandar; Aulia Rahman; Helmi Aditya Putra; Syaiful Prayogi; Luthfi Hidayat (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Diabetes mellitus (DM) is a metabolic disorder that represents a major global health burden. Its pathophysiology involves impaired insulin function, including pancreatic β-cell dysfunction, insulin resistance, defective insulin secretion, and autoimmune-mediated β-cell destruction. The identification of effective therapeutic agents and novel molecular targets remains a priority in antidiabetic drug discovery. Among potential targets, Aldose Reductase (ALR2) and Dipeptidyl Peptidase-4 (DPP-4) have attracted increasing interest because of their roles in DM progression and complications. Previous studies have suggested that 2-benzoxazolinone derivatives possess promising biological activities and may act as inhibitors of diabetes-related molecular targets. This study aimed to evaluate the interaction of selected 2-benzoxazolinone derivatives with ALR2 and DPP-4 using an in silico approach. Molecular docking was performed using PyRx integrated with AutoDock Vina, while BIOVIA Discovery Studio Visualizer and MarvinSketch were utilized for ligand preparation and interaction analysis. In addition, absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties were predicted using the pKCSM platform. The results showed that compounds 6b (-11.1 kcal/mol; 0.01 µM), 6d (-11.1 kcal/mol; 0.01 µM), and bv10 (-10.8 kcal/mol; 0.01 µM) exhibited binding affinities against ALR2 comparable to the reference inhibitor Zopolrestat (-12.2 kcal/mol; 0.001 µM). For DPP-4, compounds c26 (-7.9 kcal/mol; 1.62 µM), c4 (-7.8 kcal/mol; 1.91 µM), and c6 (-7.7 kcal/mol; 2.27 µM) demonstrated better docking performance than Vildagliptin (-6.6 kcal/mol; 14.5 µM). These compounds also showed generally favorable ADMET profiles. Therefore, they warrant further in vitro and in vivo studies as potential antidiabetic drug candidates.